PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING RATIO (NPF), FINANCING TO DEPOSIT RATIO (FDR), DAN INFLASI TERHADAP RETURN ON ASSETS (ROA) BANK MEGA SYARIAH TAHUN 2016 – 2023 - Mustaslimah, Aisa; Abdullah, Agung (Jurnal Dinamika Ekonomi Syariah, 2025)
This research is research to determine the effect of CAR, NPF, FDR, and inflation in Bank Mega Syariah return on assets (ROA) in 20, This research is quantitative research with secondary data, obtained from Bnak Mega Syariah quarterly financial report in 2016 – 2023. The research uses a purposive sampling technique for sampling, the sample used in this research is quarterly financial report data consisting of 32 CAR data, 32 NPF data, 32 FDR data and 32 inflation statistics for quarterly months data in 2016 – 2023 data Analysis techniques in research use quantitative analysis techniques using Eviews Software to process data. The result showed that the Capital Adequacy Ratio (CAR), Non Performing Ratio (NPF) and Inflation do not affect Return On Assets (ROA), only Financing to Deposit Ratio (FDR) affects Return On Assets (ROA).